ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI TRANSAKSI BERJALAN INDONESIA PERIODE 2006 – 2013 - Ramadhani Ramadhani; Murni Daulay (Departemen Ekonomi Pembangunan USU, 2014)
This study aims to analyze the factors that influence current account in Indonesia during 2006 – 2013 which use quarter data. The independence variables in this research are Interest rate, and Exchange Rate Economic Growth, and Current Account as dependent variabel.This research uses time series data, uses secondary data and methode analysis technique used in his research by using multiple linear regression analysis.The result of this research show that coefficient determination (R2) is 0,46 that has meaning independence variable (Interest rate, Exchange Rate and Economic Growth can give explanation towards on dependence variable (current account) 46 %. Meanwhile the rest are can be explained by others variable that exclude in this research. F Statistik > F tabel (7,911 > 2,99) means Interest rate, Exchange Rate Economic Growth simultanly can influence current account in indonesia at that time.Keyword: Interest rate, Exchange Rate, Economic Growth and Current Account